CONSUMER BEHAVIOR MANAGEMENT IN A METAMODERN ORGANIZATION - G. N. Ryazanova (Вестник университета)
The metamodern period presents new challenges to modern organizations. The philosophical concepts of  modernity and postmodernity, which have a kaleidoscopic effect on the mentality, values and behavior of economic  agents, transform the economic eco-system. The article considers the problems of metamodern organizations. The author has reasoned proven the need to change the management paradigm of management of industrial enterprises and service sector. The paper highlights the main directions of increasing the competitiveness of the metamodern organization. The key element of the manager is the flexibility of managing business processes and their dynamic transformation. The article reveals the tools of signal technologies that form the possibility of meeting and creating the needs of a mono-economic agent. The paper presents a model for managing consumer behavior using modern digitalization technologies.